2016
DOI: 10.7322/jhgd.122759
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sodium channel, its mutations and their spectrum of arrhythmia phenotypes

Abstract: The mechanisms of cellular excitability and propagation of electrical signals in the cardiac muscle are very important functionally and pathologically. The heart is constituted by three types of muscle: atrial, ventricular, and specialized excitatory and conducting fi bers. From a physiological and pathophysiological point of view, the conformational states of the sodium channel during heart function constitute a signifi cant aspect for the diagnosis and treatment of heart diseases. Functional states of the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Among some complications, continuous positive airway pressure is related to decrease cerebral perfusion due to increased average pressure and intracranial pressure. Others that can be cited are: trauma airway, nosocomial infections and bronchopulmonary dysplasia [23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Among some complications, continuous positive airway pressure is related to decrease cerebral perfusion due to increased average pressure and intracranial pressure. Others that can be cited are: trauma airway, nosocomial infections and bronchopulmonary dysplasia [23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypes: Mutations in SCN5A lead to a broad spectrum of phenotypes, however the SCN5A gene is not commonly involved in the pathogenesis of BrS and associated disorders. Studies have revealed significant overlap between aberrant rhythm phenotypes, and single mutations have been identified that evoke multiple rhythm disorders with common gating lesions 19 . Figure 1 shows the numerous phenotypes with SCN5A mutations.…”
Section: Paralogs or Paralogous Genesmentioning
confidence: 99%
“…Mutations in several genes, including the SCN5A, SCN1B and TRPM4 genes, can cause PCCD. Mutations in the SCN5A gene are potential etiologic factors for a number of overlapping syndromes [21]. Several other genes may be the cause when PCCD occurs with congenital heart disease.…”
Section: Epidemiologymentioning
confidence: 99%